Comparing Prophylactic Effect of Levetiracetam, Sodium Valproate, and Propranolol in Pediatric Migraine: A Randomized Clinical Trial - Fayyazi, Afshin; Pezeshki, Nasrollah; Mansuri, Hosein; Esnaashari, Farzaneh (Iranian Journal of Child Neurology, 2023)
Objectives Epidemiologic studies point to an increased prevalence of migraine in children in recent decades. Migraine treatment involves acute and prophylactic therapy. Recently, such anti-epileptic drugs as Levetiracetam have been used to treat adult migraines. The present study aimed to compare the efficacy of Levetiracetam, Sodium Valproate, and Propranolol in preventing migraine headaches in children. Material & Methods In this clinical trial, children with migraine were randomly divided into three groups. Each group consisted of 13 children. Two groups were treated with Propranolol and Sodium Valproate, respectively. Another group (the case) was treated with Levetiracetam. The patients were assessed based on headache score, PedMIDAS, and headache frequency before and three months after the intervention. Finally, the data was analyzed using descriptive and analytical statistical methods Results Levetiracetam significantly reduced the headache severity (P=0.026), frequency (P=0.024), and PedMIDAS score (P=0.001) in children with migraine. However, no significant difference was found between the three groups. The percentage of patients who experienced pain relief was detected as 69.24%, 92.31%, and 30.76% in the Propranolol, Sodium Valproate, and Levetiracetam groups, respectively. Conclusion This study concluded that Levetiracetam can be used as a migraine prophylaxis drug in children.